Rol de estrés percibido y su afrontamiento en las conducta de salud de estudiantes universitarios de Lima - Becerra Heraud, Silvia Amanda (2013)
This research investigates the role of coping in the relationship between perceived stress and health behaviors in college students. 155 students participated in the study, they were in their first years of study at a private university of Lima, their average age was 18 years, 59% were women and 10.3% worked. They were administered anonymously measures of perceived stress, styles and coping strategies and health behaviors. Hierarchical multiple regression analysis indicated that the coping variable predicts better health behaviors. The emotion-focused coping was a style that favorably affects alcohol, tobacco and other drugs intake, sleep and rest and self-care and medical care, while avoidant does unfavorably. The effect of problem-focused coping style was different depending on the health behavior involved. The strategies of using religion and seeking social support for emotional reasons were positive predictors on some health behaviors, while drug use was adverse. The results of this research can be used to help design promotion and prevention strategies in order to encourage the adoption of healthy behavior in students.